Pengaruh Edukasi Video Pijat Common Cold Bayi terhadap Pengetahuan dan Motivasi Ibu di Puskesmas Mranggen I - Fayza Aulia Agnesia; Tia Nurhanifah; Kristina Maharani (Pusat Riset dan Inovasi Nasional, 2025)
Background: In Indonesia, coughs and colds increase from 10% to 35.5%. Due to this situation, many mothers are still not fully aware of the proper handling of coughs and colds, which is further exacerbated by the issue of syrup medications containing ethylene glycol that exceed the safe dosage limits, potentially leading to kidney failure in infants. There are two types of cold treatments: pharmacological with oral medications such as powders and syrups, and non-pharmacological with common cold massage. Research objective: This quantitative research determined the effect of educational videos on common cold massage for infants on mothers' cognition and motivation in performing self-massage at the Mranggen I Public Health Care with a pre-experimental method and a one-group pre-test-post-test design. The population in this study consisted of mothers with children aged 4–12 months at the Mranggen I Public Health Care taken with a simple random sampling technique, resulting in 54 mothers. The applied instruments in this research were the Common Cold Cognition questionnaire and maternal motivation. The researchers analyzed the data using univariate and bivariate analysis, employing the Wilcoxon test to identify the non-normally distributed effect of video education on knowledge, and the paired t-test to evaluate its normal distribution effect on motivation. Research Results: Video education has an influence on mothers' cognition and motivation to perform self-massage at Mranggen I Public Health Center, with a p-value of 0.000 < 0.05. Conclusions and suggestions: Respondents, mothers with children aged 4–12 months at the Mranggen I public health care, had excellent knowledge (46.3%) and strong motivation (46.3%). The researcher expects that mothers in the Mranggen I public health care area will seek more information about common cold massages.